Adult T-Cell Leukemia/Lymphoma in the Interior of Bahia: A Case Report - Santos, Guilherme Oliveira; Dias, Jivago Souza; Passos, Rafael Feitosa do Nascimento; Siqueira, Leandro Gois (Brazilian Journal of Case Reports, 2024)
Adult T-cell leukemia/lymphoma (ATLL) is a peripheral T-cell neoplasm caused by HTLV-1, most common in endemic regions such as Japan, the Caribbean, and Latin America. This report describes the fatal case of a male patient in the state of Bahia, Brazil. ATLL is an aggressive disease with a poor prognosis, diagnosed by HTLV-1 serology and hematologic analysis. Treatment includes combination chemotherapy and antiretrovirals, but the response is usually unsatisfactory. This case highlights the importance of early diagnosis and targeted treatments. It is essential to develop more effective treatment protocols and longitudinal studies to better understand and manage the disease.